Islamic banking development and economic growth: a case of Indonesia - Meri Anggraini (Asian Journal of Islamic Management (AJIM), 2019)
Purpose: In this research, an attempt has been conducted to explore the relation between Islamic banking development and economic growth of Indonesia over the periods of 2003–2014Methodology: Two models have been formulated which are financing and deposit models to indicate the relation. The analysis are using unit root test, co-integration test, and Granger causality test within the context of VECM framework. For this purpose, financing and deposit are used as a measure of Islamic Banking development, while gross domestic product (GDP) and gross fixed capital formation (GFCF) used the indicators of economic growth.Findings: The results show that there is bi-directional causality between financing and GDP also deposit and GDP reflecting the bi-directional causality between Islamic banking development and economic growth. Further results show that there is significant short-run and long-run causality running from Islamic banking development to economic growth so as short-run and long-run causality running from economic growth to Islamic banking developmentOriginality/contributions: This is the first study to used Islamic banks in Indonesia that are listed in Bank of Indonesia in 2003-2014.